1991
DOI: 10.1056/nejm199105303242202
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Adrenergic–Antagonist Drugs in the Prevention of Gastrointestinal Bleeding in Patients with Cirrhosis and Esophageal Varices

Abstract: Propranolol and nadolol are effective in preventing first bleeding and reducing the mortality rate associated with gastrointestinal bleeding in patients with cirrhosis, regardless of severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
2
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(97 citation statements)
references
References 11 publications
5
85
2
5
Order By: Relevance
“…That this subgroup contributes to increased mortality in the former propranolol group is consistent with conclusions from a combined analysis of 589 patients, which showd a statistically significant reduction in EVH-related mortality resulting from ␤ blockers. 22 Increased mortality in the former propranolol group, if it is related to propranolol withdrawal, indirectly strengthens the argument that propranolol administration improves mortality compared with placebo in patients with gastroesophageal varices, a conclusion that few studies have been able to determine prospectively, likely secondary to type II error.…”
Section: Discussionmentioning
confidence: 82%
“…That this subgroup contributes to increased mortality in the former propranolol group is consistent with conclusions from a combined analysis of 589 patients, which showd a statistically significant reduction in EVH-related mortality resulting from ␤ blockers. 22 Increased mortality in the former propranolol group, if it is related to propranolol withdrawal, indirectly strengthens the argument that propranolol administration improves mortality compared with placebo in patients with gastroesophageal varices, a conclusion that few studies have been able to determine prospectively, likely secondary to type II error.…”
Section: Discussionmentioning
confidence: 82%
“…1 Recently, it was also shown that the efficacy of beta-blockers may be enhanced by the addition of long-acting nitrates. 2 These treatments, however, do not abolish the risk of bleeding but decrease it by half or by three quarters, respectively.…”
mentioning
confidence: 99%
“…Propranolol ca. 80-120 mg/Tag als Dauertherapie) (23). Bei Propranolol-Unverträglichkeit kann heute die endoskopische Ligatur bereits als Zweitlinientherapie zur Primärpro-phylaxe empfohlen werden (14), jedoch nicht die endoskopische Sklerosierungstherapie oder Shuntverfahren.…”
Section: Primäre Blutungsprophylaxeunclassified